Digital Collaborative Consumption in an emerging market: South African food delivery services - Tinayeshe, Shumba (University of the Witwatersrand, Johannesburg, 2023)
Many consumers have complained about food delivery services. The applications make double payments, and sometimes, the call centres are not easily accessible. Orders get mixed up, and sometimes food is delivered to the wrong addresses. Digital collaborative consumption (DCC) enables consumers to share products and services instead of owning them. A new and rapidly growing class of business models uses digitally mediated platforms to facilitate the DCC of goods and services. Smartphones' development and their rapid spread suggest that these business models could address typical low capital formation and high unemployment in emerging markets (EMs). However, although DCC is integral to daily life in emerging marketplaces, very little is known about DCC business models. The research aimed to evaluate the impact of DCC in the food delivery industry in emerging markets, focusing on South Africa. To achieve this goal, the study specifically aimed at assessing the drivers and deterrents of digital collaborative consumption in the food delivery industry, the impact of the DCC business model and develope a conceptual model which explains and predict consumer attitudes and buying intentions in EMs. Data was collected from 828 participants using validated instruments from South Africa. The theorised relations were assessed simultaneously using structural equation modelling. Models were fit to item covariance matrices using robust maximum likelihood estimation in Mplus, version 7. The research advanced the understanding of DCC to make conceptual, methodological, empirical, and practical contributions. Conceptually, the study included cognitive response and attitudes as potential mediators of DCC drivers in EMs. Empirically, the study brought together variables and relations not previously studied in EMs, including environmental influences and individual differences influencing consumer adoption. Methodologically, a new scale measuring DCC was developed from existing scales, assessed rigorously using confirmatory factor analysis, and showed good measurement properties. Home delivery, economic benefits, social benefits and security assurance strongly influenced the intention to continue using the DCC business model, while trust in the platform showed a non-significant relationship. Practically, the effect size estimates suggested that home delivery, economic benefits, Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) and security assurance have practical relevance for marketing strategies and reshaping public policy in DCC. The study recommends approaches that the research institutes, government, policymakers and business leaders can use to unlock opportunities and get new guidance on this rapidly growing business model in EMs
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa, in fulfillment of the requirements for the degree of the Doctor of Philosophy (PhD) in Management, Johannesburg 2023
Keywords: UCTD; SDG-1: No poverty